Between knowledge or story: analysis of Restu novel as a Malay literature subject text based on the idea of new literature - Hassan @ Zulkifli, Muhammad Zarif; Abdul Rani, Mohd. Zariat; Noor Muhammad, Salmah Jan (Human Resources Management Academic Research Society (HRMARS), 2023)
This study is based on the clash of two different views on the quality of the text content of Restu novel which is a Malay literature subject text. On the one hand, Restu is said to contain knowledge, while on the other hand, the quality of the narration is said to be weak. The difference of opinion regarding the quality of the content of Restu novel text can be seen as a problem that should be addressed. In order to unravel this problem, this study uses a textual analysis approach that utilizes New Literary Ideas (PB) as an analytical framework. The New Literacy Ideas (PB) offers practical analysis tools for the purpose of text analysis namely "Narrative Axis", "Narrative Space", "Discourse Fill", "Story Fill". By applying PB analysis tools, this study can detail the contents of the novels studied. This study identifies the Restu novel highlighting the "romantic dilemma" as the "Narrative Axis". Parallel to the "Narrative Axis", the analysis identified Restu's "Narrative Space" filled with "Story Filling" (Story) that manipulates several storytelling tools, especially characters and plots. The main focus of the novel is just to create a story and this tendency has resulted in the neglect of “Discourse Fill” (Knowledge) throughout the narration of the novel. This analysis refutes the claim that Restu's novel contains "knowledge", instead it only hovers at the story level and build up stories